Epidermal growth factor receptor (EGFR)‐tyrosine kinase inhibitors combined with chemotherapy in first‐line treatment in an advanced non‐small cell lung cancer patient with EGFR sensitive mutation. Issue 5 (4th July 2016) - Huang, Aimi; Li, Rong; Zhao, Jikai; Wang, Xiaofei; Jin, Bo; Niu, Yanjie; Zhang, Jie; Jiang, Liyan; Han, Baohui
Abstract : This article demonstrates a case of a lung adenocarcinoma patient in stage IV harboring an epidermal growth factor receptor (EGFR) 19 exon deletion mutation treated with 500 mg/m 2 pemetrexed and 75 mg/m 2 cisplatin on day 1, sequenced with 250 mg gefitinib on prescription on days 4–28 for six cycles as first‐line, then by gefitinib combined with pemetrexed as maintenance therapy. The patient achieved a partial response. Performance status increased from grade 2 to 1. The progression‐free survival period was 17 months. Overall survival is now over three years. Side effects of grade two liver dysfunction and dermal toxicity were tolerable. Combined gefitinib with platinum‐based chemotherapy as first‐line treatment probably benefits non‐small cell cancer patients in stage IV harboring sensitive EGFR gene mutations with a better local control rate, longer survival, and tolerable side effects.